Some Important Issues on Foreign Direct Investment in India - Kali, Dr.Sukhen; Jana, Subrata (IJRDO - Journal of Business Management, 2017)
India’s economic reforms way back in 1991 has generated strong interest in foreign investors and turning India into one of the favourite destinations for global FDI flows. According to A.T. Kearney, India ranks second in the World in terms of attractiveness for FDI. A.T. Kearney’s 2007 Global Services Locations Index ranks India as the most preferred destination in terms of financial attractiveness, people and skills availability and business environment. India is a developing country with large young labour force, massive potential market, natural and mineral resources, but the growth of the various sectors and the economy as a whole does not touch the expectation due to lack of adequate capital. In this scenario, FDI plays a vital role in enhancing the economic growth and development of the country. In the era of globalization, Foreign Direct Investment (FDI) plays an important role in the economy of any country. The ‘home’ countries want to take the advantage of the vast markets opened by industrial growth. On the other hand the ‘host’ countries want to acquire technological and managerial skills and supplement domestic savings and foreign exchange. The integration of global financial markets paves ways to this explosive growth of FDI around the world. In this paper, we are trying to point out the trend of FDI inflow in India and its impact on Indian economy